Method For Determining The Population Dynamics Of Micromammalia In The Southern Aral Sea Region (Texas Journal of Agriculture and Biological Sciences, 2025)
The article presents a method for determining the population dynamics of small mammals in the Southern Aral Sea region. Relative calculations of the number of small mammals were carried out using a Gero type recorder, using the trap-line method. To prove the quantitative influence of anthropogenic pollutants on the structure and dynamics of the Microtus Ilaeus population of the studied small mammals, mathematical models were constructed that calculate the coefficient of determination (R2), indicating the degree of influence of each selected factor.